Choledochal cyst with prenatal diagnosis and postnatal management: A case report (2022)
Cystic dilatation of the bile duct is part of a wide spectrum of biliary pathology with different etiopathogenic mechanisms. Choledochal cysts are rare malformations of the bile ducts. It is diagnosed in most cases during early childhood, although it can present at any age of life. The clinical presentation is variable and can be manifested by abdominal pain, palpable mass, cholestatic jaundice or by symptoms linked to the development of some of its complications: pancreatitis, cholangitis or rupture. The diagnosis is made through abdominal ultrasound and is completed with a ,magnetic cholangiography the recommended treatment is complete surgical resection that prevents the appearance of complications. A case of ultrasound prenatal diagnosis is presented at 29 weeks of gestation along with its evolution, management and postnatal treatment, it is also the first case in this health center located in Valle del Cauca